Intertextuality and Romance in Renaissance Drama - Hillman, Richard. author. aut Link
IX, 214 p.
Keywords: These essays apply the postmodernist theory of intertextuality to romantic drama of the English Renaissance, including work by Heywood, Beaumont and Fletcher, Ford, and especially Shakespeare. Placing the plays into dynamic relation with a wide variety of literary, cultural, and political 'intertexts' causes them to signify in ways not previously appreciated, as well as to define neglected features of the staged romance of the period. Equally important is the development of intertextuality as a critical methodology with a particular affinity for the genre and the period.